Robust Nonfragile H∞ Control of Lateral Semiactive Suspension of Rail Vehicles - Jianjun Meng; Ruxun Xu; Decang Li (Discrete Dynamics in Nature and Society)
This paper focuses on the riding comfort of railway vehicle. A nonfragile control strategy is proposed based on robust theory for semiactive suspension system. First, the rail vehicle dynamic model was simplified reasonably, the control model of rail vehicle train lateral semiactive suspension was built, which involved lateral-moving, head-shaking, and side-rolling of the vehicle body and the lateral-moving of the two bogies, and the robust nonfragile H∞ control of head-shaking and side-rolling were designed, respectively. Then the H∞ norm was used to reflect riding comfort; the sufficient conditions for the existence of robust nonfragile H∞ control were developed based on linear matrix inequality (LMI) approach. The design of a robust nonfragile H∞ control with gain perturbation was changed into an optimization issue with linear inequality constraint and a linear objective function. And then the damping effect of the robust nonfragile H∞ controller was evaluated, the wavelet packet analysis theory was used to decompose and reconstruct the acceleration signal, the fragility of the controller was analyzed, and the theory of mathematical statistics was adopted to analyze the influence of robust nonfragile H∞ controller on the probability distribution of vibration acceleration. Finally, the simulation results show that the proposed control strategy can ensure the riding comfort of railway vehicle efficiently and has a comparatively strong nonfragility.